Production of Ba(Zn1/3Nb2/3)O-3 ceramic by coprecipitation - (:unkn) unknown (ELSEVIER SCIENCE INC, 2012)
A simple coprecipitation technique was successfully applied for the preparation of pure, nanosized, single phase Ba(Zn1/3Nb2/3)O-3 microwave dielectric ceramic powders. Barium, zinc and niobium ions were precipitated as hydroxide under basic conditions using aqueous sodium hydroxide solution and single phase Ba(Zn1/3Nb2/3)O-3 ceramic was produced at 800 degrees C. TEM revealed an average particle size of around 100 nm for the calcined powders. The samples sintered at 1250 degrees C for 4 h had a relatively high density and fine grain sizes. While the dielectric constant of ceramics varied between 37.5 and 39.8 the dielectric losses were lower than 4 x 10(-3) at frequency range of 1 kHz-2 MHz between 20 and 200 degrees C. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Barium zinc niobate; Perovskite ceramics; Coprecipitation; Dielectric properties; MICROWAVE DIELECTRIC-PROPERTIES; NONSTOICHIOMETRY; ORDER